Monitoring occurrence and persistence of Listeria monocytogenes in foods and food processing environments in the Republic of Ireland - Leong, Dara; Alvarez-Ordóñez, Avelino; Jordan, Kieran (Frontiers in Microbiology, 2014)
Although rates of listeriosis are low in comparison to other foodborne pathogenic illnesses, listeriosis poses a significant risk to human health as the invasive form can have a mortality rate as high as 30%. Food processors, especially those who produce ready-to-eat products, need to be vigilant against Listeria monocytogenes, the causative pathogen of listeriosis, and as such, the occurrence of L. monocytogenes in food and in the food processing environment needs to be carefully monitored. To examine the prevalence and patterns of contamination in food processing facilities in Ireland, 48 food processors submitted 8 samples every 2 months from March 2013 to March 2014 to be analyzed for L. monocytogenes. No positive samples were detected for 38% of the processing facilities tested. Isolates found at the remaining 62% of facilities were characterized by serotyping and Pulsed Field Gel Electrophoresis (PFGE). A general L. monocytogenes prevalence of 4.6% was seen in all samples analyzed with similar rates seen in food and environmental samples. Differences in prevalence were seen across different food processors, food sectors, sampling months etc. and PFGE analysis allowed for the examination of contamination patterns and for the identification of several persistent strains. Seven of the food processing facilities tested showed contamination with persistent strains and evidence of bacterial transfer from the processing environment to food (the same pulsotype found in both) was seen in four of the food processing facilities tested.